2012
DOI: 10.1038/bmt.2012.81
|View full text |Cite
|
Sign up to set email alerts
|

Anti-thymocyte globulin for conditioning in matched unrelated donor hematopoietic cell transplantation provides comparable outcomes to matched related donor recipients

Abstract: Rabbit anti-thymocyte globulin (ATG) is used as prophylaxis against GVHD following allogeneic hematopoietic cell transplantation (HCT). At our institution, ATG is exclusively used in the conditioning of matched unrelated donor (URD) transplant recipients. A total of 50 URD HCT recipients who received ATG (ATG group) were retrospectively compared with 48 matched related donor (MRD) HCT recipients who did not receive ATG (no ATG group). There were no significant differences between the groups in rates of day 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…In a recent report, a subset analysis of the URD HSCT recipients demonstrated a significantly higher (P ¼ 0.005) mortality rate in the 10 mg/kg ATG dose recipients (18/26, 69%) than in the 7.5 mg/kg dose recipients (7/17, 29%), and this large difference stemmed from a higher day-100 mortality mostly attributable to non-relapse and non-GVHD mortality in the highdose ATG group (10/26, 39%) than in the low-dose group (1/24, Two different doses of ATG in haploidentical HSCT Y Wang et al 4%; P ¼ 0.003). 16 In the haploidentical setting, ATG in the conditioning provided a major contribution to controlling alloreactivity. 17 ATG has a key role in our unique haploidentical preparative regimen, and our recent reports validated its use in haploidentical HSCT both for patients with advanced-stage leukemia 18 and for patients with severe aplastic anemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent report, a subset analysis of the URD HSCT recipients demonstrated a significantly higher (P ¼ 0.005) mortality rate in the 10 mg/kg ATG dose recipients (18/26, 69%) than in the 7.5 mg/kg dose recipients (7/17, 29%), and this large difference stemmed from a higher day-100 mortality mostly attributable to non-relapse and non-GVHD mortality in the highdose ATG group (10/26, 39%) than in the low-dose group (1/24, Two different doses of ATG in haploidentical HSCT Y Wang et al 4%; P ¼ 0.003). 16 In the haploidentical setting, ATG in the conditioning provided a major contribution to controlling alloreactivity. 17 ATG has a key role in our unique haploidentical preparative regimen, and our recent reports validated its use in haploidentical HSCT both for patients with advanced-stage leukemia 18 and for patients with severe aplastic anemia.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,[14][15][16] A total dose of 4.5-5 mg/kg and 7.5 mg/kg ATG has been recommended in the ISD and the URD settings, respectively. In a recent report, a subset analysis of the URD HSCT recipients demonstrated a significantly higher (P ¼ 0.005) mortality rate in the 10 mg/kg ATG dose recipients (18/26, 69%) than in the 7.5 mg/kg dose recipients (7/17, 29%), and this large difference stemmed from a higher day-100 mortality mostly attributable to non-relapse and non-GVHD mortality in the highdose ATG group (10/26, 39%) than in the low-dose group (1/24, Two different doses of ATG in haploidentical HSCT Y Wang et al 4%; P ¼ 0.003).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that human, nonhuman primate, and mouse bMSCs can inhibit T-cell proliferation induced either in a MLR or by nonspecific mitogens (12). This suppression occurs regardless of the MHC of bMSCs, and the stimulator and responder lymphocytes (13,14). The immunoregulatory effect of bMSCs appears to be, at least in part, mediated by the production of cytokines such as TGFA-1 and hepatocyte growth factors and is independent of the induction of apoptosis (15).…”
mentioning
confidence: 96%
“…32 In studies comparing related donor and UD alloHSCT, it appears that in the presence of TG prophylaxis, donor relatedness is no longer a risk factor for developing cGVHD. 33,34 We hypothesised that other previously identified risk factors may also lose their utility for predicting aGVHD and cGVHD risk when TG is used, thus raising the need for new predictors of GVHD. We analysed the cumulative incidence of aGVHD and cGVHD in a large cohort of alloHSCT recipients treated with a uniform dose of TG.…”
Section: Introductionmentioning
confidence: 99%